Response of rice mutants to water stress imposed at reproductive stages - Puteh, Adam; Mondal, Mohd. Monjurul Alam (WFL Publisher, 2014)
The experiment was carried out to assess the effects of three soil moisture levels of 100, 70 and 50% field capacity (FC) on three promising rice mutants viz., RM250-172, RM250-940 and RM250-1085. The three levels of water stress were imposed at booting stage and continued up to maturity. Results indicated that morphological parameters such as plant height and leaf area, physiological parameters such as biological yield, absolute growth rate, harvest index, chlorophyll content and photosynthesis, yield attributes such as number of effective tillers hill-1, number of grains panicle-1 and 1000-grain weight were decreased with gradual increasing of water stress levels while number of non-effective tillers hill-1 and unfilled grains panicle-1 showed the reverse trend. The highest value of the above parameters was observed in 100% FC (control) and the lowest values of them were observed at 50% FC. Generally genotypes having ability to maintain high chlorophyll as well as photosynthesis under water stress was found drought tolerant in respect of dry mass production and yield attributes. Among the genotypes, the dry matter production and yield loss due to water stress was less in RM250-940 than that in the others, which further revealed that RM250-940 had a greater tolerance to moderate water stress than RM250-1723 and RM250-1085.